2021
DOI: 10.1177/24725552211008862
|View full text |Cite
|
Sign up to set email alerts
|

Brief Guide: Experimental Strategies for High-Quality Hit Selection from Small-Molecule Screening Campaigns

Abstract: Small-molecule screening is a powerful approach to identify modulators of either specific biological targets or cellular pathways with phenotypic endpoints. A myriad of assay technologies are available to assess the activity of enzymes, monitor protein–protein interactions, measure transcription factor activity in reporter assays, or detect cellular features and activities using high-content imaging. A common challenge during small-molecule screening is, however, the presence of hit compounds generating assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
12
0
4
Order By: Relevance
“…Chemoinformatics filters can help identify these frequent hitters (Baell & Holloway, 2010; Brenke et al., 2016; Schorpp et al., 2014). Hit evaluation in orthogonal and counter screens is mandatory to confirm activity and specificity (Rothenaigner & Hadian, 2021; Weber et al., 2017).…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Chemoinformatics filters can help identify these frequent hitters (Baell & Holloway, 2010; Brenke et al., 2016; Schorpp et al., 2014). Hit evaluation in orthogonal and counter screens is mandatory to confirm activity and specificity (Rothenaigner & Hadian, 2021; Weber et al., 2017).…”
Section: Commentarymentioning
confidence: 99%
“…A genuine TRAF6-Ubc13 inhibitory compound should diminish signals of different tag combinations with the same PPI of interest (here TRAF6 and Ubc13). However, it should not reduce AlphaScreen signals with other PPI pairs or in assays using the linear fusion constructs (Rothenaigner & Hadian, 2021). A study by Brenke et al (2016) used a GST-His construct to verify GST frequent hitters.…”
Section: Troubleshootingmentioning
confidence: 99%
“…As shown in Additional file 1: Fig. S1, we assessed proof of principle single-concentration drug discovery screenings of up to 114 compounds and we identified several drugs with the ability to drastically reduce the viability and stem-like properties of bone sarcoma, including several chemotherapies such as doxorubicin and etoposide (Rothenaigner et al 2021;Al Shihabi et al 2021). We also identified Pon as being highly effective at targeting OS spheroids formation using the metastatic human 143B OS cell line (Additional file 1: Fig.…”
Section: Ponatinib and Nanoparticles Physiochemical Propertiesmentioning
confidence: 99%
“…This screen used a lactate efflux assay in SKBr3 cells, with counter-screening in a lactate influx fluorometric imaging plate reader (FLIPR) assay in NCI-H358 cells to remove false positives. 14,15 These acidic hit compounds were developed into in vivo probe compounds such as AZ1422 (Figure 1), although they carried risks over human PK prediction and secondary pharmacology, specifically inhibition of bile salt export pump (BSEP) 16 and multidrug resistance-associated protein 2 (MRP2) 17,18 transporters, as well as a perceived risk of idiosyncratic toxicity from formation of an acyl glucuronide metabolite. 19,20 Zwitterionic analogues were subsequently developed and successfully optimized, although the PK properties and designing a compound with a low predicted dose to man remained a challenge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Initially, the AstraZeneca compound collection was screened for acidic hits, using the rationale that natural substrates for the monocarboxylate transporters are low-molecular-weight carboxylic acids such as lactic acid and pyruvic acid. This screen used a lactate efflux assay in SKBr3 cells, with counter-screening in a lactate influx fluorometric imaging plate reader (FLIPR) assay in NCI-H358 cells to remove false positives. , These acidic hit compounds were developed into in vivo probe compounds such as AZ1422 (Figure ), although they carried risks over human PK prediction and secondary pharmacology, specifically inhibition of bile salt export pump (BSEP) and multidrug resistance-associated protein 2 (MRP2) , transporters, as well as a perceived risk of idiosyncratic toxicity from formation of an acyl glucuronide metabolite. , Zwitterionic analogues were subsequently developed and successfully optimized, although the PK properties and designing a compound with a low predicted dose to man remained a challenge. In addition, it was subsequently found that it was difficult to establish a sufficiently high tolerated dose in nude mice to explore preclinical efficacy, and although the mechanistic reason for this lack of tolerability was not well understood, a chemically distinct series that could be optimized toward a candidate drug for clinical studies was viewed as desirable.…”
Section: Introductionmentioning
confidence: 99%